The Lancashire giant : David Shackleton, labour leader and civil servant - Martin, Ross M. (Ross Murdoch), 1929- (Liverpool University Press, 2000)
"The Lancashire Giant tell the story of a nine-year-old cotton weaver who went on to carve out two extraordinary careers for himself. In the first, David Shackleton became a truly dominating presence in the Edwardian trade union movement, was the third Member of Parliament to be elected under the banner of the Labour party, and played a critical role in the infancy of the party. His second career, begun at Winston Churchill's prompting in 1910, took him to the summit of the British civil service and to active participation in the deliberations of Lloyd George's War Cabinet." "The book is not only about Shackleton the trade unionist, parliamentarian and senior civil servant. It is also about Shackleton the man, his family and friends, his interests and feelings, his abilities, his working style, and his beliefs."--Jacket